The Influence of Participative Leadership and Digitalization of Learning on the Professional Competence - Widya Nurhayati; Nur Khoiri; Lilik Ariyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Professional competence means that teachers must be able to master teaching materials and scientific structures, compile learning tools, implement learning according to plans, carry out evaluations according to standards and carry out continuous self-development. The objectives of this study were to determine the extent of the influence of participative leadership and the digitalization of learning collectively on teachers’ professional competence. The research approach used was quantitative, and this study employed a correlational design. The study population consisted of 382 teachers, while the sample included 195 teachers. Data were collected using a questionnaire. The data analysis techniques used in this study included descriptive analysis and prerequisite tests, which consisted of normality, multicollinearity, heteroscedasticity, and linearity tests, as well as hypothesis testing through simple and multiple linear regressions. The results of the study indicated that (1) the correlation between participative leadership and teachers’ professional competence was 0.862. The influence of participative leadership had a significant effect on the variable of teachers’ professional competence by 74.3%. (2) The correlation between the digitalization of learning and teachers’ professional competence was 0.827. The influence of the digitalization of learning had a significant effect on the variable of teachers’ professional competence by 68.5%. (3) The combined influence of participative leadership and the digitalization of learning on teachers’ professional competence was expressed in the equation Ŷ = 8.916 + 0.862 X1 + 0.539 X2. The value of the correlation coefficient (r) was 0.891. The coefficient of determination for the influence of variables X1 and X2 on Y was 79.4%. The conclusion of this study was that there was a significant influence of participative leadership and the digitalization of learning on teachers’ professional competence by 79.4%.